2015
DOI: 10.1136/jfprhc-2015-101177
|View full text |Cite
|
Sign up to set email alerts
|

Shifting abortion care from a hospital to a community sexual and reproductive health care setting

Abstract: This study suggests that provision of outpatient EMA in a community SRH setting is as safe as that delivered from a hospital setting, and that women are similarly satisfied with the information they receive about abortion from each setting. More abortion assessment and outpatient EMA services in Great Britain could shift from hospital to community SRH settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Although there may be concerns that abortion services might place undue pressure on women to choose LARC post-abortion, anonymous surveys of women requesting an abortion at the study settings have shown that the vast majority (over 95%) of women do not feel under pressure to choose a particular method of contraception and value the opportunity to discuss this 16 23…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there may be concerns that abortion services might place undue pressure on women to choose LARC post-abortion, anonymous surveys of women requesting an abortion at the study settings have shown that the vast majority (over 95%) of women do not feel under pressure to choose a particular method of contraception and value the opportunity to discuss this 16 23…”
Section: Discussionmentioning
confidence: 99%
“…Both the hospital and SRH services retained the same centralised referral service that allocated appointments to either site on a first available basis 16. This was an administrative service that interacted with health service staff only (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Women attending the Chalmers Centre abortion service have an ultrasound scan to confirm the location and gestation of their pregnancy 11. If the uterus appears to be empty, they are asked to provide a urine sample to conduct a confirmatory high-sensitivity urinary pregnancy test (positive at >25 IU/L hCG).…”
Section: Methodsmentioning
confidence: 99%
“…With this in mind, we introduced a hCG POCT system to our community-based NHS abortion service (Chalmers Centre, NHS Lothian) in an urban UK setting 11. This service provides care for approximately 2000 women each year requesting termination of pregnancy 1.…”
Section: Introductionmentioning
confidence: 99%